Surface Functionalization of TiO2 with Plant Extracts and their Combined Antimicrobial Activities Against E. faecalis and E. Coli - Maurya, Archana; Chauhan, Pratima; Mishra, Amita; Pandey, Abhay K. (Journal of Research Updates in Polymer Science, 2012)
The aim of this study is to enhance the antibacterial activity of TiO2 by pure plant extracts of Bauhinia variegata and Tinospora. cordifolia by making a composite of plant extract and TiO2. Plant extracts, TiO2 and plant extracts/TiO2 composites were investigated against two bacterial strain Enterococcus faecalis and Escherichia coli. X-ray diffraction investigations have confirmed the presence of TiO2 nanoparticles in the plant extract/TiO2 nanocomposites. UV-visible investigations have shown an enhanced photocatalytic activity of plant extract/TiO2 nanocomposites compared to that of pure TiO2 and pure plant extract. Plant extract/TiO2 nanocomposites have shown various level of antibacterial activity on different test microorganisms. The highest antibacterial potentiality expressed in terms of zone of inhibition (ZOI) in mm was exhibited by the aqueous extract of Bauhinia variegata /TiO2 (45 mm against Enterococcus faecalis and 30 mm against Escherichia coli) and benzene extract of Tinospora cordifolia /TiO2 (26 mm) nanocomposites. This is the first study on these types of bio-nano composite materials and it serves as basis for further research on these types of composite materials as a potent antibacterial agent.